Following a half-century oceanographic data gap in the northern Canadian Arctic Archipelago: multidecadal variability of the Pacific water throughflow - Igor A. Dmitrenko; Sergei A. Kirillov; David G. Babb; Tonya Burgers; Qiang Wang; Sergey Danilov; Dorthe Dahl-Jensen; Dorthe Dahl-Jensen (Frontiers in Marine Science)
The Canadian Arctic Archipelago (CAA) serves as a major conduit between the Arctic Ocean and the North Atlantic. The Nansen Sound fiord system, which encapsulates Nansen Sound, Greely Fiord, Eureka Sound and several surrounding fiords, forms the northernmost oceanographic passageway through the CAA. Due to hostile ice conditions, the area has been understudied since the original oceanographic surveys were conducted in the 1960s and 1970s. The historic data highlighted a very weak signal of the relatively fresh Pacific-derived water (PW). Here, we present new oceanographic observations, including PW tracers, and contrast them against the historic data. Salinity profiles taken in 2024 show significant freshening as compared to 1976. This freshening is attributed to enhanced presence of PW in the area. We suggest that changes in the Arctic Oscillation impact the export gateways of PW from the Arctic Ocean, with the recent switch to a positive phase enhancing the outflow of cool and less saline PW through the CAA. Overall, this provides a first glimpse into variability of the freshwater flow through the straits of the northern CAA.